Management Information System Implementation Doyan Drinks Using K-Means - M Ridho Ramadhan; Yusuf Ramadhan Nasution; Aninda Muliani Harahap (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Technological developments are currently very influential in business collaboration, to be precise in Doyan's drink, Doyan is a local beverage brand that has difficulty determining franchise partnerships to determine the type of package in the strategy of location, area, and facilities of prospective franchisees, by implementing a Management Information System on Doyan can determine the type of franchise based on the required criteria, this study uses the Waterfal method in designing management information systems and uses the K-Means algorithm in determining the type of franchise that suits the needs of the candidate. K-Means functions to cluster the franchise type criteria data that will produce the closest value so that the output can choose and determine the more appropriate type of franchise package, and the store can manage product sales, stock, and attendance at all franchise branches